Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Pengembangan SDM Di PT Pertamina EP Klamono Oil (Kabupaten Sorong) - Anastasya Natalia Latuasan; Arce Y. Ferdinandus; Yusuf Aditya Prasetyo (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
In this study there are two variables, namely variable X1 (Leadership), X2 (Work Motivation) and variable Y (HR Development). This research was conducted to determine the leadership and work motivation of PT Pertamina EP Klamono Oil employees, PT Pertamina EP Klamono Oil HR development, and the influence of leadership and work motivation on HR development at PT Pertamina EP Klamono Oil, Sorong Regency. The data used are primary data collected through observation, distribution of questionnaires, and interviews. The hypothesis of this study is that there is an influence of leadership and work motivation on human resource development at PT Pertamina EP Klamono Oil, Sorong Regency. To measure the influence of these variables used multiple linear regression and the coefficient of determination with the help of the IBM SPSS 23 computer application program. Based on the results of data analysis using statistical methods, namely multiple linear regression, this can be seen from the value of the multiple linear regression coefficient for (X1) of 0.314 and (X2) of 0.219, in addition to the value for > alpha 0.05 from the test results of the coefficient of determination (R2) it can be seen that the R Square or the coefficient of determination is 0.056, and the Adjusted R Square value is 0.006 – 0.6% meaning HR development can be explained by leadership and work motivation of 0.6%. While the remaining 99.4% can be explained by other factors such as work discipline, compensation, quality of work, etc. so it can be concluded that the variables of leadership (X1) and work motivation (X2) have a significant influence on the HR development variable (Y). The results of this study indicate that leadership has a positive and significant effect on human resource development at PT Pertamina EP Klamono Oil Klamono Oil, Sorong Regency.